Pencarian Pola Akses Pengunjung Toko Online Menggunakan Weighted Graph Web Usage Mining - Helmy (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The growth of online stores is proportional to theincrease in web usage data that is generated. Web Usage Mining can generate useful information based on web usage data. This information is required by the owner of the online shop to find information on frequently accessed pages and demanded items by visitors. This study is using Weighted Graph Web Usage Mining method for generating online shoppers access patterns. This methode include collecting web usage data when client using AJAX interface in real time, ¬ pre-processing to generate the database traversal and discovering pattern with Weighted Frequent Patterns Mining methods. The results show that Weighted Graph Web Usage Mining can generate informations about frequently accessed pages and demanded items by visitors in a given period based on visitors access pattern.